Pengaruh Profitabilitas, Cash Holding, Dan Nilai Perusahaan Terhadap Perataan Laba - Amalia Haniftian; Dillak, Vaya Juliana (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This research was conducted to find out how the simultaneous and partial influence between profitability, cash holding, and company value on income smoothing in companies in the LQ45 index listed on the Indonesia Stock Exchange in 2014-2018. The method in this study uses quantitative methods. The hypothesis in this study was tested using logistic regression analysis using SPSS 23.0 software. The sampling technique used in this study was a purposive sampling technique that produced 20 samples of selected companies within a period of 5 years so that 100 sample units of companies in the LQ45 index were listed on the Indonesia Stock Exchange in 2014-2018. The results of this study indicate that the variable profitability, cash holding, and firm value simultaneously have a significant effect on income smoothing. Partially, profitability and firm value do not significantly influence income smoothing. While the cash holding variable has a significant effect on the positive direction of income smoothing.